Disparity in Jack v Jack: Judicial Overreach or a Just Result at Long Last? - Shaw, Susannah (Victoria University of Wellington Law Review, 2014)
This article discusses the approach taken to enhanced income awards under s 15 of the Property (Relationships) Act 1976 in the recent decision of the High Court in Jack v Jack. The Court upheld the Family Court's award of 70 per cent of the relationship property pool to Mrs Jack to compensate her for economic disparity arising out of the division of functions in the relationship, on the basis she helped Mr Jack enhance his career and sacrificed her own earning potential. The author argues that in upholding the Family Court's findings on causation and accepting the broad brush assessment of quantum, the Court has increased the chances of a successful claim for an enhanced income award. In light of the underutilisation of the enhanced income aspect of s 15, this decision is a welcome step towards the fulfilment of the provision's aims.